Improving Students’ Critical Thinking Skills through Project-Based Learning (PBL) in General English for Pre Intermediate 4 Class in LB LIA Palembang: A Classroom Action Research - Fitria, Trianda; Tahrun, Tahrun (Jurnal Pendidikan Tambusai, 2021)
This study aims to find out whether applying Project-Based Learning can improve students’ Critical Thinking skills in General English for Pre Intermediate 4 class in LB LIA Palembang, a Non Formal English Language Institution in Palembang. The study was conducted as a classroom action research. There were 20 students who participated as the samples of the research. The data were collected through observation, questionnaire and interview. Then, the data were analyzed. The results showed 17 out of 20 students (85%) get the desired level of Critical Thinking skills. Based on the interview, all students have positive understanding of Project-Based Learning model. In conclusion, PBL has an influence in improving students’ critical thinking skills. Further study needs to be conducted to give more positive impact to society.